SILICA EXTRACTION FROM RICE HUSK AS A SLOW RELEASE FERTILIZER USING MICROWAVE ASSISTED EXTRACTION - Indriani D.W.; Indriani D.W.; Sumarlan S.H.; Teresia L. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The utilization of waste as raw materials is one of the alternatives in applying the "zero waste" principal. Rice husk is one of the wastes of rice plantation which has very high silica content at around 80-90%. The extraction of silica from rice husk can be used to make slow release fertilizer. Slow release fertilizer is a fertilizer with a nutrient release mechanism that periodically follows the pattern of nutrient absorption by plants. This study aims to optimize rice husk tablets formulation by extraction using Microwave Assisted Extraction (MAE) and to determine the physical and chemical properties of the results of rice husk extract tablets. This study used a Completely Randomized Design (CRD) with two factors, namely the concentration of KOH with variations in solvents 2.5%, 5%, and 7.5% and warm-up durations of 5, 7.5 and 10 minutes. The largest hardness value was 3,356 kgf in 7.5% KOH with 10 minutes in microwave. The largest yield of silica was 7.5% KOH with the longest heating time of 10 minutes of 5.30%. Through XRF analysis, it was found that the largest silica value was 6.51% at 5% KOH with a heating time of 5 minutes. Based on the comparison with the conventional heating method, the results of extraction did not reach optimum results of silica extract (21.8%), whereas in this research the yield obtained was 6.51%. Thus, based on these results, heating using microwave did not produce optimal silica results.